EJSD 2018
DOI: 10.30689/ejsd2018:67.1650-9544
|View full text |Cite
|
Sign up to set email alerts
|

Participation according to the law?: The research-based knowledge on citizen participation in Norwegian municipal planning

Abstract: Citizen participation is enshrined in the Norwegian Planning and Building Act (PBA) 1985 and accentuated by the 2008 revision of the PBA. In this article, we ask if the research on participation in municipal planning is sufficient to draw conclusions on whether the Act is effective with regard to both the spirit and the letter of the law. The guiding framework for the analysis is based on the concepts of input and output legitimacy and the distinction between 'tidy' and 'untidy' participation. The analysis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Citizen participation in planning is given a high priority in the Norwegian Planning and Building Act in terms of general rules for consultations, publicity and information to ensure transparency, predictability and the participation of all affected parties (Ministry of Local Government and Modernisation, 2008;Ringholm, Nyseth, & Gro, 2018). As early as in the 1985 version of the Act, the Ministry of Environment emphasised that 'for the planning, it is an advantage that views can be identified as early as possible, avoiding the process coming to a standstill because vital points of view are presented too late in the process' (Ministry of Climate and Environment, 1985).…”
Section: The Norwegian Planning Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Citizen participation in planning is given a high priority in the Norwegian Planning and Building Act in terms of general rules for consultations, publicity and information to ensure transparency, predictability and the participation of all affected parties (Ministry of Local Government and Modernisation, 2008;Ringholm, Nyseth, & Gro, 2018). As early as in the 1985 version of the Act, the Ministry of Environment emphasised that 'for the planning, it is an advantage that views can be identified as early as possible, avoiding the process coming to a standstill because vital points of view are presented too late in the process' (Ministry of Climate and Environment, 1985).…”
Section: The Norwegian Planning Systemmentioning
confidence: 99%
“…While local zoning plans in Norway were traditionally predominately devised by public authorities, currently approximately 90% of urban zoning plans are initiated by private developers (Falleth et al, 2010). In 2013, 67% of local politicians reported that they were always in contact with developers in early planning stages (Ringholm et al, 2018). Ringholm et al (2018) state that detailed zoning plan processes tend to be non-transparent and inaccessible, even in cases where some level of participation is documented.…”
Section: The Norwegian Planning Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Public participation is important to ensure well-informed decisions, engagement and ownership of both democratic and community-based development (KMD, 2014). Although public participation has been a legal requirement in Norway since it was introduced in the Planning and Building Act in 1985, many have argued that the practice is far from satisfactory (Ringholm et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar barriers have been found specifically in a Norwegian planning context. Ringholm et al (2018) noted that citizens described the planning process as inaccessible and lacking transparency. Further, citizens taking part in public participation processes seldom consist of a representative sample of the population, resulting in the dominance of a limited number of opinions (Klausen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%